2012
DOI: 10.1002/ptr.4636
|View full text |Cite
|
Sign up to set email alerts
|

Xanthohumol Induces Different Cytotoxicity and Apoptotic Pathways in Malignant and Normal Astrocytes

Abstract: Cytotoxicity and the mechanisms of cell death induced by xanthohumol (XN) were compared in normal and cancerous human cells as the differences may be relevant for the potential use of XN in cancer therapy. The cancer cells seemed to be more susceptible to the cytotoxicity of XN than normal cells, but a significant difference was observed only in astrocytic cells. XN induced a higher rate of apoptosis in glioblastoma cells than in normal astrocytes, which was associated with activation of p53 and an elevated Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…The capacity of xanthohumol to induce intracellular ROS was shown to activate the mitochondrial apoptotic pathway in human malignant glioblastoma cells (9). Other studies support this fi nding, showing that it is able to inhibit the growth and to induce apoptosis in several cancer cell lines: prostate (10), ovarian (11), glioblastoma and malignant astrocytes (9,12), lymphocytic leukaemia (13) and colon (14).…”
Section: Dose-dependent Protective and Inductive Effects Of Xanthohummentioning
confidence: 81%
See 1 more Smart Citation
“…The capacity of xanthohumol to induce intracellular ROS was shown to activate the mitochondrial apoptotic pathway in human malignant glioblastoma cells (9). Other studies support this fi nding, showing that it is able to inhibit the growth and to induce apoptosis in several cancer cell lines: prostate (10), ovarian (11), glioblastoma and malignant astrocytes (9,12), lymphocytic leukaemia (13) and colon (14).…”
Section: Dose-dependent Protective and Inductive Effects Of Xanthohummentioning
confidence: 81%
“…Anticarcinogenic and antioxidant properties of xanthohumol present in Humulus lupulus L. have been reported before (3,5,(9)(10)(11)(12)(13)(14)(37)(38)(39). However, scarce information is available on the eff ect of xanthohumol on yeast cells.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in accordance with those reported by Pan et al (27), which demonstrated that xanthohumol induces apoptosis of human colon cancer cells via caspase-3, -8 and -9. Furthermore, Zajc et al (15) reported that xanthohumol induces different cytotoxic and apoptotic pathways via Bax/Bcl-2 in malignant and normal astrocytes. Kunnimalaiyaan et al (28) demonstrated that xanthohumol inhibits induces apoptosis via the anti-apoptotic markers, survivin, cyclin D1 and Mcl-1, in hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies investigating xanthohumol have predominantly focused on the prevention and treatment of cancer (13,14). Studies have demonstrated that xanthohumol inhibits tumor cell growth of colon cancer, prostate cancer, cervical cancer, liver cancer and leukemia cells (15)(16)(17). Therefore, the aim of the present study was to investigate the effect of xanthohumol on the proliferation of human laryngeal squamous cell carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, the brewing industry has been interested in producing XN-enriched beers, mainly due to the recognized health benefits. XN possesses a large spectrum of chemopreventive mechanisms in a wide variety of cancers, such as breast [4], colon [5], colorectal [6], brain [7], ovarian [8], leukemia [9,10] and prostate [11][12][13] cancer, with no effects on major organ functions after oral administration [14]. A recent study reported that XN-supplemented beer helps reducing inflammation, oxidative stress and angiogenesis, ameliorating the wound healing process [15].…”
Section: Introductionmentioning
confidence: 99%